Kebermaknaan Salam Dalam Bisnis - Nuradi Nuradi; Husnul Khatimah; Halim Faqihuddin Annasr (Jurnal Ilmiah Ekonomi Islam, 2023)
The greeting which in Arabic is called "At-tahiyyah" is a very noble sentence that has been abandoned by many Muslims. Greeting comes from the word "salima" which is the opening word when meeting and greeting which means safety, peace, blessing. This research was conducted to find the meaning contained in the greeting and its implications for business. This type of research is in the form of library research with a qualitative approach, namely focusing on existing reasoning and logical abilities, for example, cause and effect relationships, if and then, actions result in reactions and the like. The results of the research show that greetings in Islam are not only mere conversation starters or small talk but more than that in business activities it will provide a sense of security and safety in the business activities carried out, sending down the grace of the Creator and also blessings in these business activities.